Genetically Proxied Autoimmune Diseases and the Risk of Facial Aging - Zhang Z; Li M; Geng Y; Wang W; Wang W; Shao Y (Dove Medical Press, 2024)
Zhanyi Zhang,1 Mengyuan Li,2 Yujia Geng,1 Wangshu Wang,1 Weihao Wang,1 Ying Shao1 1Department of Plastic and Reconstructive Surgery, the First Hospital of Jilin University, Changchun, Jilin Province, 130000, People's Republic of China; 2College of Chinese Medicinal Materials, Jilin Agricultural University, Changchun, Jilin Province, 130118, People's Republic of ChinaCorrespondence: Ying Shao, Department of Plastic and Reconstructive Surgery, the First Hospital of Jilin University, Changchun, Jilin Province, 130000, People's Republic of China, Email shao_ying@jlu.edu.cnPurpose: Previous studies have suggested a relationship between autoimmune diseases and the risk of facial skin aging. However, evidence from population-based studies on this topic is limited, leaving the causal association between these factors unknown. This study aimed to systematically evaluate the causal effects of 18 autoimmune diseases on the risk of facial skin aging, aim of providing strategies to mitigate early facial aging in patients with autoimmune diseases.Patients and Methods: We conducted univariate Mendelian randomization (UVMR) analyses to examine the causal relationship between 18 autoimmune diseases and facial aging using publicly available summary data from genome-wide association studies (GWASs). We also conducted multivariate Mendelian randomization (MVMR) analyses to adjust for confounding factors, including smoking, alcohol consumption, and body mass index (BMI).Results: The main inverse variance weighted (IVW) method revealed that genetically proxied ankylosing spondylitis (AS) (OR 1.017; 95% CI: 1.003- 1.031; P=0.018), sicca syndrome (SS) (OR 1.008; 95% CI: 1.005- 1.011; P= 2.66× 10− 6), systemic lupus erythematosus (SLE) (OR 1.006; 95% 1.001- 1.011; P=0.014), multiple sclerosis (MS) (OR 1.004; 95% CI: 1.001- 1.007; P=0.021), primary sclerosing cholangitis (PSC) (OR 1.002; 95% CI: 1.000- 1.004; P=0.023), and celiac disease (CeD) (OR 1.002; 95% CI: 1.001- 1.004; P=0.009) were significantly associated with higher risk of facial aging. After adjusting for potential confounding factors, the association persisted between AS, SLE, and CeD.Conclusion: These findings indicated that autoimmune diseases play a causal role in facial skin aging. Therefore, patients with autoimmune diseases should take appropriate measures to prevent early facial aging.Keywords: autoimmune disease, facial aging, Mendelian randomization, ankylosing spondylitis, systemic lupus erythematosus, celiac disease